Estado del arte del uso de bioles en la producción agropecuaria del Ecuador. - Iza Cabay, Paola Mercedes (2021)
This research was carried out by analyzing the results of 17 scientific studies focused on the application of bioles in Ecuador; to identify the microorganisms, nutrients, and effects that they presented, in each of the experiments. Determining that the presence of nitrogen 0.03% to 1.80% and potassium 0.25% to 1.6%, in lesser quantity ions of (Na, Mg, Zn, Cu, Fe, P, Ca, Mo) the variations are not very noticeable, however, their presence is always important to nourish the plant. And a pH ranging from 5.0 to 8.19 within the bioles. The pH value is considered of utmost importance since the availability of the nutrients that will be supplied to the plants will directly depend on this. At present, the use of chemical fertilizers in agricultural production has increased notably, farmers are dependent on them to be able to obtain products without pests, with better yields in their crops, and to have the necessary nutrients for the soil. The trend of the use of organic products has increased notably globally. In agricultural production, bioles, liquid fertilizers produced thanks to the anaerobic fermentation of organic matter, have been used, some of which have shown efficiency in crop production, to obtain quality products with rich nutrients for people feeding.